The Impact of the COVID-19 Pandemic on the Needs and Lived Experiences of Intimate Partner Violence Survivors in the United States: Advocate Perspectives. (October 2022) - Ragavan, Maya I.; Risser, Lauren; Duplessis, Virginia; DeGue, Sarah; Villaveces, Andrés; Hurley, Tammy P.; Chang, Judy; Miller, Elizabeth; Randell, Kimberly A.
We explored the challenges and lived experiences of intimate partner violence (IPV) survivors during the COVID-19 pandemic by interviewing 53 U.S.-based IPV advocates between June and November 2020. Advocates described how the COVID-19 pandemic limited survivors' abilities to meet their basic needs. The pandemic was also described as being used by abusive partners to perpetrate control and has created unique safety and harm reduction challenges. IPV survivors experienced compounding challenges due to structural inequities. IPV must be considered by local, state, and federal governments when developing disaster planning policies and practices, including in the context of pandemics.